Rethinking Islamic law: conceptual premises and strategic framework - Haneef, Sayed Sikandar Shah (LexisNexis, 2009)
Islamic law as articulated by Muslim jurists of the classical time carries a heavy baggage of pre-modem era both at thought and methodological levels. Historical factors conditioning the past jurists' understanding of textual.proofs and their urge to provide legal solutions to day-to-day expediencies of human lives was acknowledged by the legal dictum, yuristic views changes with the changes in time and space'. However, this thesis seems not to have been fully appreciated by mainstream conservative legal scholars who, by and large cling onto traditional methodology of reconstructing Islamic law to offer contemporay solutions. This paper therefore, argues that Muslim scholars have to rethink beyond the traditional way if they are desirous of constructing a modem system of law for contemporary Muslims.